Halal Lifestyle Education in Food and Fashion Aspects for Today's Teenagers in Pandansari Village Batang - Nurul Khairunnisa'; Azzahroh, Mutiara; Khasanah, Ismatul (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
Halal lifestyle awareness in Indonesia, especially teenagers, shows that most still lack understanding of halal lifestyles and halal product criteria. The purpose of this education is to socialize as well as raise awareness about the halal lifestyle movement. It is hoped that the audience will gain knowledge related to the Halal lifestyle, especially in the fields of food, fashion and finance, because halal is an important factor that must be considered by Muslims in living life, both in choosing products and choosing ways in lifestyle. The method used is to deliver material directly to the audience, carry out education in the form of counseling and discussion, and evaluation to increase the awareness of teenagers in the form of socialization. The results of this activity can be seen an increase in halal lifestyle awareness and show positive movements from teenagers in Pandansari Village, Batang. Changes that exist, for example, a teenager who did not wear a hijab when participating in community service activities, after participating in community service activities, the teenager was willing to wear a hijab because she had received positive values from the material. hijab because she has gained positive values from the material presented. In addition, some teenagers have become smarter in choosing halal products in accordance with Islamic law.